Pacto Nacional pela Alfabetização na Idade Certa : implicações de uma política pública nacional numa escola de Porto Alegre - Schneider, Carolina Chagas (2017)
The present work analyzes the implementation of the National Pact for Literacy at the Right Age by reflecting on what outcomes result from a literacy national public policy in a socially vulnerable community in the outskirts of Porto Alegre (Rio Grande do Sul, Brazil). This work is characterized as a case study research with a qualitative and descriptive approach. The study is focused on a specific school reality in the city of Porto Alegre, aiming to identify in the school context the results of the implementation of the National Pact for Literacy at the Right Age, which included a deep immersion in the context. The data was collected through semistructured interviews, document research and observations registered in the “teacher’s class notes”. The results of the research were observed in two broad categories the limits and possibilities of the program studied, the main subcategories were within the limits: difficulties of initial adherence of the teachers in the formation of PACTO and lack of continuity of the program. In the possibilities category the main subcategories were: quality of the course and improvement in the quality of teaching. The main theorists who supported the research on literacy are: Mortatti, Soares, Tfouni, Morais, and Ferreiro. The theorists researched on public policies were Gontijo and Akkari. The research also included official documents from the Brazilian Education Ministry and City Education Department of Porto Alegre.